3D DATA GRAVITY MODELING FOR IDENTIFICATION OF THE FORMATION STRUCTURE OF THE HYDROCARBON BASIN IN THE BAJUBANG REGION, JAMBI PROVINCE - Ira Kusuma Dewi; Fitria Puspitasari; Nasri M Z; Agustyadi Martha (Engineering Faculty Universitas Lampung, 2020)
Jambi is an area that has natural resources in the form of petroleum, one of which is the Bajubang region. Bajubang is located in the Jambi Sub Basin where ripe hydrocarbons are visible in the Talang Akar Formation. Petroleum exploration continues to run out of oil reserves. To find the presence of a sedimentary basin that has stopped, it can be done by measuring the gravity method. The basic concept of this method is to measure the geographical variation of an area on the earth's surface and corrected through the prevailing measurements or prices. The purpose of this research is to determine the geological structure pattern that causes the formation of sub-basins that indicate the presence of hydrocarbons and describe the subsurface conditions using forward modeling and backward modeling. Based on the modeling results found as many as 7 sub basins sediment. The height and fault structures are identified in the subsurface model. Based on the regional anomaly map shows the presence between the basin and the elevation. The fault structure, anticline and sub-basins are found which are expected to produce hydrocarbons.